Smart And Inclusive Campus: Pengembangan Sarana dan Prasarana untuk Kampus Ramah Disabilitas - Cut Meuthia Rani; Zhilli Izzadati Khairuni; Yuslinda Yuslinda; Irene Santa Maria Simamora; Yunisah Putri Damanik (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Inclusive higher education in Indonesia still faces significant challenges in fulfilling the rights of persons with disabilities to access equal education. This article presents the concept of a "Smart and Inclusive Campus" with a Universal Design for Learning (UDL) approach and the integration of sensory-based digital technology to create a more inclusive campus environment. A literature study and analysis of inclusive education policies were conducted to identify accessibility gaps and formulate strategies for developing campus facilities and infrastructure. The results of the study indicate that a combination of universal open space design, mobile-based assistive technology, digital navigation systems, and reinforcement of physical infrastructure can enhance the academic and social participation of students with disabilities. Implementing this concept requires the active involvement of various parties, including the government, educational institutions, the private sector, and disability communities. By adopting this innovative approach, higher education institutions are expected to create a learning environment that is equal, adaptive, and supportive of all students.